A reeleição de vereadores evangélicos em Belém de 1992 a 2008: conexão, regra do jogo e comunicação com as bases - SILVA, Luiz Henrique da (Universidade Federal do Pará, 2014)
In 2004 was elected the councilors who composed the Municipality of Bethlehem, having been occupied the vacancies left by those who were not reelected. This framework allowed the reelection of affirmation and strengthening of political parties, for several mandates, political representation and remain with seat in Parliament Hall. This is the case of the Workers Party (PT), the Brazilian Democratic Movement Party (PMDB), the Party of Brazilian Social Democracy (PSDB), Brazilian Labor Party (PTB) among others. This group has been represented in Parliament Hall for a long uninterrupted period. The champion is the renewal of mandate Councilman Paul Pastor Queiroz of IEQ (Foursquare Gospel Church) who is in his fourth term. Then comes the Cllr Baptist Pastor Raul UCKG (Universal Church of the Kingdom of God) who is in his third term and Councilman Iran Moraes of AD (Assembly of God) who is in his third term. The starting point of the research, part of the conditions suggested by Pereira and Renno (2001) and supported by Downs (1958) that the central goal of a politician is to seek reelection. Anthony Downs believes that the individual within their rationality, has the ability to interpret their choices within a logic of possible alternatives. He does not let himself be seduced by the movements of the candidates, but makes his choice within the alternative that presents itself but retains the rational choices. It is noticed that over the years, lawmakers evangelicals have shown greater strength in some denominations to remain in parliament for several terms. This is the case of parliamentarians of the Foursquare Gospel Church, Seventh Day Adventist, the Universal Kingdom of God, Assembly of God. The process of continuous renewal of mandate is based on leadership support and services provided to internal segments of Churches.